Chapter 4 Who should decide for critically ill neonates and how? The grey zone in neonatal treatment decisions - Wilkinson, Dominic (The Federation Press, 2016)
This chapter distinguishes between essential features of the zone of parental discretion and the longstanding concept of a grey zone in neonatal treatment decision-making. The grey zone has traditionally described a gestational age range where the outcomes of medical treatment for newborn infants are uncertain, and therefore parents have discretion to choose between resuscitation or palliative care options. In contrast, the ZPD refers to a space where parents may make decisions for their child (not restricted to newborns) even if their decisions conflict with the decisions a clinician would make. A key difference between the two zones is that the boundaries of the grey zone are defined on the basis of published evidence about medical outcomes, whereas the boundaries of the ZPD are based on the broader but arguably vaguer notion of harm to the particular child. The grey zone has usually been defined in terms of gestational age. Wilkinson argues instead for a prognosis-based grey zone in neonatal treatment decision-making, which incorporates a range of prognostic factors rather than focusing solely on gestational age.